Health behaviors and perception of risks associated with the use of e-cigarettes and other tobacco substitutes among secondary school students in the Podkarpackie Province - Fryc, Ewelina; Charzyńska-Gula, Marianna (Journal of Education, Health and Sport, 2026)
Abstract Introduction: The popularity of e-cigarettes/tobacco heaters/snus has been steadily growing in recent years. They are increasingly replacing traditional cigarettes. This is most often the result of users’ belief that they are healthier and safer than traditional cigarettes, but also a result of fashion. This is a serious problem among today’s youth. Research objective: The aim of the study was to learn about the awareness and behaviors of young people in the Podkarpackie Province related to e-cigarettes and other substitutes for traditional tobacco smoking. Material and methods: A diagnostic survey method was used with a questionnaire technique and an original electronic questionnaire. The study surveyed 310 secondary school students (women: 52.58%; men: 47.42%) from general secondary schools, technical schools, vocational schools, and vocational schools. Results: Nearly 40% of the students surveyed do not smoke tobacco, either traditionally or electronically. E-smokers account for 23.87%, traditional cigarettes 11.29%, snus 5.48%, and tobacco heaters 3.23%. The study group also included ex-smokers (5.81% - former traditional smokers, 4.19% -former electronic smokers), as well as passive tobacco smokers (24 students - 7.74%). The general health awareness of the surveyed students is at a fairly low level, with an average level of knowledge about the consequences of smoking and tobacco use. Conclusions: The scale of use of traditional smoking substitutes is a serious and growing problem. Active education on the harmful effects of various forms of tobacco smoking should be an integral part of young people’s lives, both at school and at home.